Ripple pattern formation on silicon carbide surfaces by low-energy ion-beam erosion. Issue 1 (1st January 2023) - Gupta, Divya; Umapathy, G.R.; Singhal, Rahul; Aggarwal, Sanjeev
Abstract: A versatile experimental facility air insulated high current medium energy 200 kV Ion Accelerator, with the terminal voltage in the range of 30-200 kV has been running successfully at Ion Beam Centre, KUK for carry out multifarious experiments in material science and surface physics. This system offers single charge state, switching magnet with five exit ports and large area irradiation/implantation using hollow cathode ion source. Ion beam induced structures on the surfaces of semiconductors have potential applications in photonics, magnetic devices, photovoltaics, and surface-wetting tailoring etc. In this regard, silicon carbide (SiC) is a fascinating wide-band gap semiconductor for high-temperature, high-power and high-frequency applications. In this work, fabrication of ripple patterns is carried out on the SiC surfaces using 80 keV Ar + ion beam for different fluences at oblique incidence of 50 0 . AFM study demonstrates that ripple wavelength and amplitude, ordering and homogeneity of these patterns vary linearly with argon ion fluence. The formation of such surface structures is attributed to the preferential sputtering of silicon in comparison to carbon. The evolution of high degrees of order is explained with the help of existing formalisms of coupling between surface topography and preferential sputtering.